2020
DOI: 10.1371/journal.pone.0235393
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Monte Carlo sampling methods for metabolic network models

Abstract: Reaction rates (fluxes) in a metabolic network can be analyzed using constraint-based modeling which imposes a steady state assumption on the system. In a deterministic formulation of the problem the steady state assumption has to be fulfilled exactly, and the observed fluxes are included in the model without accounting for experimental noise. One can relax the steady state constraint, and also include experimental noise in the model, through a stochastic formulation of the problem. Uniform sampling of fluxes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Furthermore, these studies relied on biased optimization strategies without also exploring the entirety of solution space throughout different growth phases. However, research has demonstrated how random flux sampling can analyze metabolic differences across multiple conditions while eliminating the need for assuming an optimal flux state [ 28 , 38 , 45 ]. The main disadvantage of using a random sampling approach is that there is a link missing between the fluxes for a particular solution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies relied on biased optimization strategies without also exploring the entirety of solution space throughout different growth phases. However, research has demonstrated how random flux sampling can analyze metabolic differences across multiple conditions while eliminating the need for assuming an optimal flux state [ 28 , 38 , 45 ]. The main disadvantage of using a random sampling approach is that there is a link missing between the fluxes for a particular solution.…”
Section: Discussionmentioning
confidence: 99%
“…We thus opted to perform further analysis only on these models. Since the basic version of flux balance analysis (FBA) is unable to provide unique solutions, we opted to analyse the activity of the observed metabolic reactions using flux sampling using the artificial centering hit-and-run (ACHR) algorithm [50] . It was performed on the models extracted with the FASTCORE algorithm to obtain the mean values of reaction fluxes in each of the models.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the dynamical response of the models, we performed flux sampling using the artificial centering hit-and-run (ACHR) algorithm [50] on the extracted models. 1000 flux samples were generated for each of the models, and the mean flux of each reaction was used to identify the reactions that are either down- or up-regulated in pairwise comparisons of specific factors (diet, gender, and genotype) according to Spearman’s rank correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its simplicity and the genuine uniform distribution that it provides, this algorithm cannot be used with high dimensional spaces and irregular shaped polytopes given that the fraction of rejected samples increases dramatically with the number of metabolic fluxes considered in the network. Other algorithms have been (and are still) developed to circumvent this problem [41,42]. Among the oldest and simplest methods, hit-and-run algorithms [43] consist of Markov Chain Monte Carlo methods that sample the convex polytope via some specific random walk.…”
Section: Dealing With the Underdeterminacymentioning
confidence: 99%
“…Regarding these criteria, refs. [41,42] have shown that CHRR outperforms ACHR and OPTGP. Recently, refs.…”
Section: Some Further Perspectives On Sampling Algorithmsmentioning
confidence: 99%